Survey of young women knowledge about menopause and prevention of its complication in Kerman healthy centers - Nikpour s (Iran University of Medical Sciences, 1991)
this research is a cross sectional study conducted to survey of young women knowledge about menopause and prevention of its complication in Kerman healthy centers. A questionnaire including 36 three optional items prepared by researcher and given to subject via reference to healthy centers. Result show that most subjects had not favorable knowledge about menopause and prevention of its complication. Result also show that education level of female and their spouses had no effect on their knowledge about menopause and prevention of its complication.